Measuring Digital and Traditional Financial Inclusion in Egypt: A New Index (International Journal of Applied Research in Management and Economics, 2021)
Digital finance has witnessed rapid development in the last few years that might threaten the way traditional financial services are being used. It creates new opportunities for small businesses and low – income groups that have no or limited access to formal financial services. Therefore, digital financial inclusion plays an important role in enhancing a country`s financial inclusion, meeting some sustainable development goals and achieving higher economic growth. Although few studies took the attempt to measure the inclusiveness of the financial system in Egypt, however, no study did quantify the financial inclusion for Egypt. This paper aims to fill in this gap by contributing to the literature in two ways; first, by introducing a novel comprehensive financial inclusion index for the first time using a three – stage principle component analysis (PCA). Second, we build two separate indices; traditional and digital financial inclusion indices through combining access, usage, and barriers indicators for traditional financial index while for digital financial index we combined access and usage indicators. Findings revealed that both “traditional financial index” and “digital financial index” are equally important in explaining the overall financial inclusion of Egypt and thus, digital finance is seen as a complement rather than a substitute to the traditional financial services. Moreover; our results also revealed that although Egypt has low level of digital financial inclusion (0.31), digital finance is playing a significant and positive role in achieving greater financial inclusion as evidenced by improving the overall index from low (0.41) to relatively high inclusion level (0.52).